Photographic manual of regional orthopaedic and neurological tests - Cipriano, Joseph J. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2010)
"Now in its Fifth Edition, this Photographic Manual of Regional Orthopaedic and Neurologic Tests describes in step-by-step fashion how to perform these tests. Each chapter begins with a decision tree of the orthopaedic examination of an anatomic area, followed by a brief description of the anatomic area, usually with an accompanying drawing. The presentation of each test begins with a clinical description and a box of clinical signs and symptoms, followed by a brief description of the procedure with a photograph demonstrating the position of the clinician and the patient. The author then presents a brief rationale for the test and suggests diagnostic imaging procedures where appropriate. An accompanying DVD demonstrates a typical examination"--Provided by publisher.
(Publisher-supplied data) 1 CLINICAL ASSESSMENT PROTOCOL -- 2 POSTURAL ASSESSMENT 15 / by Steven P. Weiniger, DC -- 3 CERVICAL ORTHOPAEDIC TESTS -- 4 CERVICAL NERVE ROOT LESIONS -- 5 SHOULDER ORTHOPAEDIC TESTS -- 6 ELBOW ORTHOPAEDIC TESTS -- 7 WRIST ORTHOPAEDIC TESTS -- 8 HAND ORTHOPAEDIC TESTS -- 9 THORACIC ORTHOPAEDIC TESTS -- 10 LUMBAR ORTHOPAEDIC TESTS -- 11 LUMBAR NERVE ROOT LESIONS -- 12 SACROILIAC ORTHOPAEDIC TESTS -- 13 HIP JOINT ORTHOPAEDIC TESTS -- 14 KNEE ORTHOPAEDIC TESTS -- 15 ANKLE ORTHOPAEDIC TESTS -- 16 MISCELLANEOUS ORTHOPAEDIC TESTS -- 17 CRANIAL NERVES -- 18 Reflexes -- 19 CEREBELLAR FUNCTION TESTS.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Physical orthopedic tests -- Atlases; Neurologic examination -- Atlases; Electronic books